Cognitive processes: metacognition as a learning process - Hurtado Velit, Ana Lucía (2017)
Metacognition as a learning process allows our mind to have the ability to turn on itself and analyze our own thoughts and our knowledge. For this reason, it is important that the teachinglearning processes are strengthened in order to achieve a satisfactory learning in students and give them a better knowledge of their abilities. In this regard, the present article will address the topic of metacognition, its dimensions, metacognitive strategies and metacognition classes in order to provide a contribution to Education at all levels.